Sociological Approaches in Islamic Education Study - Zainal Arifin (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Educational Sociology refers to the application of sociological knowledge, thinking techniques, and data collection in educational investigations. Thus the sociology of education learns about the educational process as social interaction, schools as social groups, and as social institutions. This type of research is library research, namely research whose main object is books or other sources of literature. That is, data are sought and found through literature review from books that are relevant to the discussion. Models of sociological analysis of education include 4 types of analysis, (1) analysis of functional structural models with figures Emile Durkeim and Talcott Parsons, (2) analysis of conflict models with figures of S. Bowles and H. Gintis and Louis Althuser, (3) analysis critical sociology model with the figures Paulo Freire and Ivan Illich and (4) English and US version of Micro Level Education Analysis Keywords: Sociological Theory, Islamic Education, Sociological analysis models